2012
DOI: 10.1186/1472-6963-12-177
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of dental care: what do patients value?

Abstract: BackgroundDentistry in Australia combines business and health care service, that is, the majority of patients pay money for tangible dental procedures such as fluoride applications, dental radiographs, dental fillings, crowns, and dentures among others. There is evidence that patients question dentists’ behaviours and attitudes during a dental visit when those highly technical procedures are performed. However, little is known about how patients’ experience dental care as a whole. This paper illustrates the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
13

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 19 publications
2
71
0
13
Order By: Relevance
“…To improve patients' perception of dental care services, the Nigerian government needs to invest more funds in upgrading the infrastructure, equipment and instruments used to deliver dental care. According to Sbaraini et al [31] , outpatient dental care services differs from other outpatient health care services because its focused on provision of tangible treatments such as the procedures performed in the mouth of patients at the dental clinic, need for follow-up visits for other physical interventions. This is in contrast to a visit to a doctor where the patient's focus might be receiving health advice, routine exams and/or drug prescriptions [31] .…”
Section: Discussionmentioning
confidence: 99%
“…To improve patients' perception of dental care services, the Nigerian government needs to invest more funds in upgrading the infrastructure, equipment and instruments used to deliver dental care. According to Sbaraini et al [31] , outpatient dental care services differs from other outpatient health care services because its focused on provision of tangible treatments such as the procedures performed in the mouth of patients at the dental clinic, need for follow-up visits for other physical interventions. This is in contrast to a visit to a doctor where the patient's focus might be receiving health advice, routine exams and/or drug prescriptions [31] .…”
Section: Discussionmentioning
confidence: 99%
“…21,22 It positively affects daily interaction between dentist and patient, such as in the improvement of patient's health, the establishment of doctor-patient relationship, and increase in patients' satisfaction. 5,23 In contrast, a lack of communication may…”
Section: Discussionmentioning
confidence: 99%
“…It is not surprising that investigations on factors affecting patient satisfaction found that when it comes to dentist characteristics, patients tend to rank interpersonal relationship as of utmost importance. 4,5 This emphasizes the importance of soft skills among dental clinicians. Students who have the ability to acquire and subsequently master such skills can gain further understanding of patients' needs, engage in tasks that will fulfill patients' expectations, and enable them to gain more control in their academic development and growth.…”
Section: Introductionmentioning
confidence: 99%
“…Ailesel faktörler arasında; ebeveynlerin inanç sistemleri ve tutumları, çocuğun mizacı (örneğin; diş fırçalamaya direnç göstermesi), ebeveyn okur yazarlığının az olması ve mevcut eği-tim materyallerini eksik anlaması, optimal ağız sağlığı ve koruyucu yöntemler hakkında ebeveynlerin yetersiz bilgisi, ağız bakımını öncelikli hâle getirmeyi zorlaştıran maddi zorluklar, dental anksiyete ve korkular, düşük maliyetli dental bakıma ulaşım zorluğu diğer sorumluluklarla kıyas-landığında, evdeki ağız bakım aktivitelerinin zaman alıcı ve düşük öncelikli kabul edilmesi yer almaktadır. [91][92][93][94] Çevresel faktörler ise sağlık sigortasının olmayışı, ebeveynin çalışma saatleri ya da diğer sorumluluklarıyla çakışmayacak diş randevusu zamanı ayarlayamama/uygun olmayan klinik çalışma saatleri, ebeveynlerin çocukların okulda devamsızlık yapmasını istememesi, dental hizmetin olduğu bölgelere ulaşım araçlarının eksikliği ve coğrafi problemler, sağlık hizmetlerinin hastaları yönlendirme konusunda karmaşık olması ve sosyo-ekonomik ve kültürel ayrımcılık şeklinde sıralanabilmektedir. 95 Diş çürükleri açısından yüksek risk grubunda olan pek çok aile, dental bakıma ulaşma konusu kadar, tedavi planına ya da evde bakım önerilerine itaat etme konusunda da zorluklar yaşamaktadır.…”
Section: Eçç'ni̇n öNlenmesi̇nde Karşilaşilan Engellerunclassified